System Implementation for the Soft Start Operation of a Doubly-Fed Induction Motor - Warachart Suwan-ngam (My University, 2024)
This project aims at system implementation for the soft start operation of a doubly-fed induction motor (DFIM) based on stator flux vector control. In this paper, the theory is briefly discussed. The simulation is performed using PLECS software to validate the hypothesis. A 5 kW wound rotor induction motor (WRIM) mechanically coupled with a simulated load is setup for the experiment. The STM32F407 microcontroller is applied to control the experimental system. Moreover, the Modbus protocol is applied for communication between the microcontroller and the computer using RS485 standard. The problem about rotor angle correction before enabling the MSC, which does not appear in the simulation, is seriously discussed. The experimental results do substantiate the proposed method and can be practically applied to the real system.
Keywords: Motor soft starter; Multilevel Inverters and Converters